2013
DOI: 10.1116/1.4821186
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of sputtered neutrals and ions and investigation of their roles on the plasma properties during rf magnetron sputtering of Zn and ZnO targets

Abstract: Langmuir probe and optical absorption spectroscopy measurements were used to determine the line-integrated electron density, electron temperature, and number density of Ar atoms in metastable 3P2 and 3P0 levels in a 5 mTorr, rf magnetron sputtering plasmas used for the deposition of ZnO-based thin films. While the average electron energy and density of Ar atoms in 3P2 and 3P0 excited states were fairly independent of self-bias voltage, the Ar 3P2-to-electron number density ratio decreased by approximately a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…The population of 3p 5 4s states is consistent with the data reported by L. Maaloul et al [5] and by L. Maaloul and L. Stafford [19] in RF magnetron sputtering. For atomic metastable states of Ar, the density of Ar 1s5 is of the order of 10 9 cm -3 and of Ar 1s3 is of the order of 10 8 cm -3 ; for atomic resonant states of Ar, the densities of Ar 1s4 and Ar 1s2 are of the order of 10 8 cm -3 .…”
Section: Densities Of Statessupporting
confidence: 91%
See 2 more Smart Citations
“…The population of 3p 5 4s states is consistent with the data reported by L. Maaloul et al [5] and by L. Maaloul and L. Stafford [19] in RF magnetron sputtering. For atomic metastable states of Ar, the density of Ar 1s5 is of the order of 10 9 cm -3 and of Ar 1s3 is of the order of 10 8 cm -3 ; for atomic resonant states of Ar, the densities of Ar 1s4 and Ar 1s2 are of the order of 10 8 cm -3 .…”
Section: Densities Of Statessupporting
confidence: 91%
“…-The dominant process is the Penning ionization with sputtered Zn atoms, its relative contribution is about 90 % at NZn = 10 11 cm -3 . The importance of Penning ionization reactions on plasma kinetics during magnetron sputtering with Zn targets illustrated above is in good agreement with the work of L. Maaloul and L. Stafford [19]. Indeed, the authors have shown that in plasmas characterized by relatively low charged particle densities, Penning ionization reactions are the dominant mechanisms for pulverized particles.…”
Section: Densities Of Statessupporting
confidence: 88%
See 1 more Smart Citation
“…1 The results are also in excellent agreement with those obtained in previous actinometry measurements on Zn atoms using Ar as the actinometer gas. 21 To gain further insights into the respective roles of Zn metastable atoms and Zn ground state atoms on the plasma deposition dynamics of ZnO-based thin films, the results presented above were compared to spectroscopic ellipsometry measurements of the deposition rate on a Si substrate located at 12 cm from the ZnO target. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 In the present study, the discharge was sustained in pure Ar gas at a pressure of 5 mTorr using ZnO as the sputtering target (Kurt J Lesker). The self-bias voltage resulting from the 13.56 MHz electric field applied to the magnetron apparatus (provided by Plasmionique, Canada) was varied between À115 and À300 V by adjusting the absorbed (i.e., incident minus reflected) RF power.…”
Section: Experimental Setup and Diagnosticsmentioning
confidence: 99%